1993
DOI: 10.1002/j.1460-2075.1993.tb06008.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of an endotoxin-neutralizing protein from the horseshoe crab, Limulus anti-LPS factor, at 1.5 A resolution.

Abstract: Lipopolysaccharide (LPS), or endotoxin, is the major mediator of septic shock, a serious complication of Gram‐negative bacterial infections in humans. Molecules that bind LPS and neutralize its biological effects or enhance its clearance could have important clinical applications. Limulus anti‐LPS factor (LALF) binds LPS tightly, and, in animal models, reduces mortality when administered before or after LPS challenge or bacterial infection. Here we present the high resolution structure of a recombinant LALF. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
186
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(195 citation statements)
references
References 39 publications
8
186
1
Order By: Relevance
“…The two typical structures indicated that EsALF was an amphipathic factor and its crystal structure possibly was a hairpin loop just like Limulus ALF [37]. Phylogenetic analysis further revealed that the EsALF was close matched to ALFs from crabs and shrimps (the bootstrap was 67% to shrimps and 40% to crabs).…”
Section: Discussionmentioning
confidence: 92%
“…The two typical structures indicated that EsALF was an amphipathic factor and its crystal structure possibly was a hairpin loop just like Limulus ALF [37]. Phylogenetic analysis further revealed that the EsALF was close matched to ALFs from crabs and shrimps (the bootstrap was 67% to shrimps and 40% to crabs).…”
Section: Discussionmentioning
confidence: 92%
“…Limulus anti-LPS factor (LALF) is a protein from the horseshoe crab with high potential to block endotoxin-mediated activities in animals (17)(18)(19)(20). Both BPI and LALF crystal structures are known, and the LALF analysis revealed a detailed view of a potential endotoxin-binding site (21). The site consists of the aa 31-52 and is characterized by an alternating series of positively charged and hydrophobic residues forming a positively charged amphipathic loop (21).…”
Section: E Ndotoxin Is a Major Constituent Of The Outer Membrane Ofmentioning
confidence: 99%
“…Both BPI and LALF crystal structures are known, and the LALF analysis revealed a detailed view of a potential endotoxin-binding site (21). The site consists of the aa 31-52 and is characterized by an alternating series of positively charged and hydrophobic residues forming a positively charged amphipathic loop (21). Two other endotoxin-binding proteins from mammals, namely bactericidal/permeability increasing protein (BPI) and LPS binding protein (LBP), were proposed to have a similar endotoxin binding site (21).…”
Section: E Ndotoxin Is a Major Constituent Of The Outer Membrane Ofmentioning
confidence: 99%
See 2 more Smart Citations